Effect of Different Stocking Densities on Behavior of Common Carp (Cyprinus carpio) in Duhok Province, Kurdistan Region, Iraq - Mizory, Firas A.; Hussein, Nizar J.; Ali, Nareen S. A.; Hussein, Salam R. (International Journal of Scientific Research in Biological Sciences, 2020)
An experiment was conducted to checking up the effects of overcrowding on common carp Cyprinus carpio prosperity using their behavior. Nine concrete ponds were used with three replication ponds for each density (3.6 m length, 2.7 m width, 1.00 m depth and 0.80 m water level) with water volume (7.776 m3) for each pond. Number of fishes per each pond was 4 (low density), 8 (medium density) and 12 (high density), weighing 1000 g. Water volume for each fish in ponds was (1.944 m3, 0.972 m3, 0.648 m3 respectively). Fish behavior was recorded by immediate sampling with frequency and duration. Each pond was observed directly on the front of pond. Results exposed that there was a significant difference (P<0.01) of time spent feeding between treatments. In addition, a significant difference (P<0.01) was found in resting time between treatments besides there was a worthy of difference of swimming time between different stocking densities. Time spent in swimming was recorded for high stocking density fishes more than other groups significantly (P<0.01), and significantly less time spent resting. Air breathing had significantly (P<0.01) for higher stocking density more than other stocking densities. In high stocking density all aggressive behaviors were found to be more significantly; bites and attacks (P<0.05), threatening and submission (P<0.01). It`s not recommend to stock less than two fishes per meter for carp at concrete ponds